Explore The Struggle Of Francois Emile Van Der Linde And Darius Silitonga In Bukit Wungkal Against Dutch Military Aggression II Through Whisp - Fahri, Ardian; Fahreza, M. Mifta Yoga (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2025)
The purpose of this study is to know and understand the integration of the Local History of thestruggle of Francois Emile Van Der Linde and Darius Silitonga in the Second Dutch Military Revolution.The research is a Historical Research Method to understand Local History, as well as an R&D ResearchMethod to create a WHISP. In this study, Data Collection Techniques were carried out by Observation,Interview, Documentation and Literature. The Data Analysis technique uses source triangulation with thestages of Data Reduction, Data Presentation, Verification. The results of the study show that the local historycomponents of the struggle of Francois Emile Van Der Linde and Darius Silitonga in the Second DutchMilitary Coup can be integrated in History Learning, namely Resistance Strategy and Technique, History ofToponymy of Silitonga Hill and Analysis of Struggle Locations. The values that can be exemplified from thestruggle are the spirit in defending Indonesia's independence, love for the homeland and nation, willingnessto make sacrifices for the nation, mutual respect and cooperation. The integration of Local History in HistoryLearning can be done by paying attention to the material contained in the student learning syllabus, thisintegration can be done through creating a website using Wix by developing Web History in SpectraPerspective.Keywords: Integration, History Learning, Local History